Perfect apples or sustainable production?—Consumer perspectives from Germany - Ronja Hueppe; Katrin Zander (Journal of Consumer Behaviour, 2023)
In recent years, environmental problems, such as resource depletion and biodiversity loss, have come to the forefront of society's attention. Consumption of fruits and vegetables from extensive production systems could decrease food loss and increase biodiversity and more sustainable resource use. However, fruits and vegetables from extensive production systems are not always of perfect external quality, and hence, rejected by consumers. To increase acceptance of imperfect fruits, this study aims to better understand consumers' perceptions of different levels of imperfections, using apples as an example. An online survey with 842 German consumers investigated associations, important apple-buying criteria, organic apple consumption, socio-demographics, and willingness to pay (WTP) for apples with different levels of imperfection. The latter is investigated via contingent valuation. A multiple linear regression was calculated for each level of imperfection. Results show that consumers' WTP for apples differed depending on the level of external imperfections. The majority of consumers accepted slightly imperfect apples; a noticeable share would even buy them at the same price as flawless apples. Apples with heavy imperfections were mainly accepted by consumers who had sustainable buying criteria. To increase acceptance, it is important to tell consumers that their food choice can make an impact on how apples are produced, that imperfect apples come from more sustainable production systems and are of perfect internal quality. And finally, it is important to give specific advice that buying these apples can help to increase sustainable resource use and biodiversity.
Keywords: 320